Cytosolic dsDNA of mitochondrial origin induces cytotoxicity and neurodegeneration in cellular and zebrafish models of Parkinson’s disease - Hideaki Matsui; Junko Itô; Noriko Matsui; Tamayo Uechi; Osamu Onodera; Akiyoshi Kakita (2021)
Abstract Mitochondrial dysfunction and lysosomal dysfunction have been implicated in Parkinson’s disease (PD), but the links between these dysfunctions in PD pathogenesis are still largely unknown. Here we report that cytosolic dsDNA of mitochondrial origin escaping from lysosomal degradation was shown to induce cytotoxicity in cultured cells and PD phenotypes in vivo. The depletion of PINK1, GBA and/or ATP13A2 causes increases in cytosolic dsDNA of mitochondrial origin and induces type I interferon (IFN) responses and cell death in cultured cell lines. These phenotypes are rescued by the overexpression of DNase II, a lysosomal DNase that degrades discarded mitochondrial DNA, or the depletion of IFI16, which acts as a sensor for cytosolic dsDNA of mitochondrial origin. Reducing the abundance of cytosolic dsDNA by overexpressing human DNase II ameliorates movement disorders and dopaminergic cell loss in gba mutant PD model zebrafish. Furthermore, IFI16 and cytosolic dsDNA puncta of mitochondrial origin accumulate in the brain of patients with PD. These results support a common causative role for the cytosolic leakage of mitochondrial DNA in PD pathogenesis.